Economic Perspectives of MSMEs on Peer-to-Peer Lending as Business Capital Financing in Asahan Regency - Sari, Ok. Putri Ananda; Harahap, Muhammad Ikhsan; Hermain, Hendra (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to determine the perceptions of MSMEs in Asahan Regency towards peer-to-peer lending-based capital financing services. This service is presented as a digital financing alternative that offers ease and speed in accessing capital, especially for MSMEs that have difficulty obtaining capital from conventional financing. This study used a qualitative approach with interviews with 10 MSMEs, consisting of five users and five non-users of P2P lending services. Data analysis was conducted using Nvivo 12 Pro software to identify perceptions based on five components: ease, benefits, risks, challenges, and trust. The results show that MSMEs who have used P2P lending services have a positive perception of the ease and benefits directly experienced from using P2P lending services. However, they also face risks and challenges in using P2P lending services. In contrast, MSMEs who have never used P2P lending services tend to have perceptions dominated by doubt, worry, and ignorance due to lack of experience. User trust is formed through direct experience, while non-user trust relies more on reputation and information from their surroundings.